2006
DOI: 10.1515/pteridines.2006.17.4.121
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Trauma and Immune Activation after a Downhill Marathon (Tyrolean Speed Marathon)

Abstract: Prolonged physical exercise is associated with multiple changes in the immune status indicating an acute phase response and an activation of the immune system. Eccentric muscle activation (e.g. downhill running) induces micro-trauma of skeletal muscles thus inducing an inflammatory response. At present there are no data to which extent the immune system is activated after a downhill marathon run and if there arc any correlations between immune activation and markers for muscle damage or functional impairment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(15 reference statements)
0
3
1
Order By: Relevance
“…One likely mechanism could be an exercise triggered systemic inflammatory response. We observed specific changes after the Tyrolean Speed Marathon which are indicative for an activation of the immune system, but did not find differences in inflammatory markers after eccentric activity compared to concentric activity [8]. Moreover, several studies have found an association between high levels of (NT-pro) BNP and ischemia.…”
contrasting
confidence: 62%
“…One likely mechanism could be an exercise triggered systemic inflammatory response. We observed specific changes after the Tyrolean Speed Marathon which are indicative for an activation of the immune system, but did not find differences in inflammatory markers after eccentric activity compared to concentric activity [8]. Moreover, several studies have found an association between high levels of (NT-pro) BNP and ischemia.…”
contrasting
confidence: 62%
“…The current study identified a lack of statistical change throughout the week of training, suggesting that no one day provided more inflammation than another, even though they were statistically elevated above control values on specific days. Previous studies have identified immediate increases in plasma neopterin and other inflammatory cytokines post-exercise [31,49,50] suggesting the delay in sample collection in the current study may have masked the full extent of total immune system activation. Since muscle damage and subsequently inflammation occur following resistance exercise, the delay in sample collection still allows communication between T-cells and macrophages and the production of neopterin and 7,8-dihydroneopterin at sites of muscle damage.…”
Section: Daymentioning
confidence: 76%
“…The communication of T cells and macrophages and the subsequent release of neopterin makes it an effective marker of immune system activation and inflammation [21,29]. Several studies have identified the rise of neopterin in plasma and urine following exercise [30][31][32][33]. Our thought is that the damage to muscle as a result of eccentric loading and hypertrophy training will increase the amount of macrophages present at these sites, and subsequently produce higher concentrations of 7,8-dihydroneopterin which can be oxidized to neopterin.…”
Section: Neopterin and 78-dihydroneopterinmentioning
confidence: 99%
“…120 mins) and immediately post-game (game 1: 37.3 ± 10.1 min, game 2: 41.6 ± 13.8 min, game 3: 33.9 ± 16.4 min) during 3 selected home games of the 2013 ITM Cup. Immediate post-game sample collection was chosen based on all markers peaking within an hour after exercise [16,48,60]. Fluids and food were provided by the team (750 ml water, 375 ml coconut water, 200 ml protein shake, fruit, chicken sushi, soup and fried chicken) and each player had been asked to do a 10 min cold bath post-game.…”
Section: Experimental Protocol and Sample Collectionmentioning
confidence: 99%